Talent Link - Ahmad Saadeh; Ahmed Awwad (My University, 2025)
Many individuals, such as students, graduates, employees, and freelancers, find it difficult to get job or training tasks that are compatible with their skill sets. Conversely, companies find it hard to discover the appropriate talent in an effective way. The objective of this project is to develop a system that utilizes a smart matching algorithm to compare existing competencies with the competencies that are required so that employment, training, and contracting with freelancers can be made more efficient. Main Features: 1. User and Company Profiles: Individuals can create profiles showcasing skills, work preferences, and past projects. Companies can post opportunities (jobs, internships, freelance projects) and specify required skills. 2. Smart Matching System: Automatically matches individuals with suitable opportunities and companies with qualified candidates based on skills, experience, and location. 3. Instant Application and Communication: Enables direct applications, instant messaging, and in-platform video calls for interviews. 4. Freelancer and Project Support: Allows freelancers to advertise services and companies to hire for specific projects. 5. Job and Internship Map: Displays nearby opportunities on a map for location-based searches. 6. Notifications: Sends alerts for matching opportunities, new messages, and interview invitations. 7. Rating and Feedback System: Enables individuals and companies to rate each other after completing work or training. This platform is not just a job board but a smart recruitment and project system that saves time and effort for individuals and companies through automated matching, freelancer support, and direct communication.